Historical Progression of Nepal’s Economic Interests in Foreign Policy and Economic Diplomacy - Khanal, Prem Raj (Journal of APF Command and Staff College, 2025)
Economic diplomacy emphasizes the significance of global economic issues like trade, investment and finance, which has been employed in various forms within foreign policy directives of states. The subject is relevant as the Nepali government has been prescribing greater priority to economic diplomacy, seen within the several periodic plans that the paper has analyzed. The primary objective of the study is to identify the development of the idea through several foreign policy doctrines in Nepal’s history, as it progressed from a monarchy to a federal republic, ascertaining both the growing usage of the term and its relevance in policy mechanisms, and the evolving functions of state representatives. A qualitative method has been employed that utilizes an analytical approach when discerning the different dimensions of economic diplomacy in Nepal’s foreign policy. Focusing primarily on a rigorous review of literature, and also through content analysis of official state documents, the study has simultaneously assessed the perceptions of intellectuals and policy practitioners. This paper has found that historically economic interests have in many pivotal cases driven Nepal’s foreign policy agendas in its immediate neighborhood, post-unification, and also later when it expanded its presence in the globalized world order. However, in contemporary diplomatic practices, while Nepal has made several strides in carving economic diplomacy as a cornerstone of its foreign policy agenda, political transitions and inadequate incorporation of long-standing recommendations from stakeholders, coupled with lagging growth remain as significant challenges, which require further contemplation.